SECONDARY BONE-JOINT BLOCK IN IN A NEWBORN BABY’S MUSCULAR TORTICOLLIS - Загородникова, Ольга Александровна; Коновалова, Нина Геннадьевна (Mother and Baby in Kuzbass, 2023)
A clinical case of the sternocleidomastoid muscle’s birth injury and C0-C1 block combination and emerging torticollis in a baby first days life also manual therapy with subsequent immobilization and evaluation of results in dynamics is presented.It is concluded that the diagnosis and treatment of the sternocleidomastoid muscle’s injury in the first days of life provide a complete restoration of the anatomical relationships in the cervical region and the symmetry of reflex activitythat determines the babe’s development in accordance the age norm.
Keywords: birth trauma; muscular torticollis; functional osteoarticular block; manual diagnostics and therapy